(untitled) (Rehabilitation and Recreation, 2024)
Competition systems in professional sports are constantly updated under the influence of social, economic, demographic, and political factors. The competition system that developed in professional golf has turned today into a grand spectacle on the one hand and a profitable business on the other. It is important to identify the specifics of the formation of a sport in different age periods and the factors that influenced it. Objective. Justify competition models in professional golf for various historical periods of the formation and development of this sport Methods. The main material of the work was data from scientific and popular science sources of information, which highlighted important facts regarding the development of golf and competitions in it in different historical periods, as well as detailed works in which the specifics of the current stage of development of the competition system in professional golf are determined. The key scientific research method is modeling. Results. At various stages of the professional golf development, the following groups and competition models were highlighted: a non-systemic group: one-tournament (1860–1894), twotournament (1895–1920), three-tournament (1921–1933), four-tournament (1934–1941) models; a discretesystemic group: four-tournament (1946–1967) model; a systemic group: tour (1968–1978), Grand Slam (1979–2014), tour-hierarchical (2015–2019) models; a desystemic-adaptive group: tour-hierarchical model (2020–2021); a resystemic group: tour-hierarchical model (from 2022 up to now). Conclusion. The data obtained in this study can supplement the system of knowledge about competition systems in professional sports and, accordingly, allow specialists to acquire new competencies in this field.